Microbial Proteases Applications - Razzaq, Abdul; Shamsi, Sadia; Ali, Arfan; Ali, Qurban; Sajjad, Muhammad; Malik, Arif; Ashraf, Muhammad (Frontiers in Bioengineering and Biotechnology, 2019)
The use of chemicals around the globe in different industries has been increased tremendously affecting the health of people. The modern world is intending towards the replacement of these noxious chemicals with environmentally friendly products for the betterment of life on the planet. This has been a prime objective for the scientist to establish enzymatic processes in spite of chemical processes. Various enzymes specifically microbial proteases are considered the most essentially used in different corporate sectors like textile, detergent, leather, feed, waste and others. Proteases with respect to physiological and commercial roles hold a pivotal position. As they are performing synthetic and degradative functions, proteases are found ubiquitously such as in plants, animals and microbes. Among different producers of proteases, Bacillus sp. are mostly commercially exploited microbe for proteases. Proteases are successfully considered as an alternative to the chemicals and an eco-friendly indicator for nature or surrounding. Evolutionary relationship among acidic, neutral and alkaline proteases has been analyzed based on their protein sequences but still there is a paucity of information that regulates the diversity in their specificity. Researchers are looking for microbial proteases as they can tolerate harsh conditions, ways to prevent autoproteolytic activity, stability in optimum pH and substrate specificity. The current review is focusing on the comparison among different proteases and the current problems facing during production and application at industrial level. Deciphering these issues would enable us to promote microbial proteases economically and commercially around the world.